Contingency factors and strategic management accounting usage in the Algerian medium-sized enterprises - Bouzourine, Abdelhalim (2017)
This study aims to examine the effect of the selected contingent factors (e.g. perceived environmental uncertainty, market orientation and, technology) on the practice of strategic management accounting usage in medium-sized manufacturing companies in Algerian. The research framework is based on contingency theory. This study uses a survey method, and questionnaires are distributed to the top management of medium-sized manufacturing companies in Algeria to provide some evidence supporting the effect of contingent factors on the adoption of strategic management accounting techniques. To analyse the data collected, the Smart-PLS 3 used to test the hypotheses in this study. The results found that the factors from the contingent factors that have a positive and significant effect on strategic management accounting usage are perceived environmental uncertainty and market orientation, while, technology is not significant to strategic management accounting usage. The results provide implication to theoretical and practical. The findings contribute to the body of knowledge in strategic management accounting and contingency theory. The results provide evidence to top management in terms of the important factors that influence strategic management accounting usage.